2013
DOI: 10.1177/1708538113478741
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of β-aminopropionitrile-induced aortic dissection model in rats by different administration and dosage

Abstract: This study compared three β-aminopropionitrile (BAPN) treatment rats to find the optimal BAPN model for thoracic aortic dissection and aneurysm in one study. Sixty rats were divided into five groups: control, injected control, 0.25% and 0.4% BAPN treatment (orally), and 667 mg/kg/day BAPN injection subcutaneously. Incidence of aortic dissection and aneurysm, aortic weight and diameter were measured directly. Thickness of media and area of aorta were measured by hematoxylin and eosin and Victoria blue staining.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
1
20
1
Order By: Relevance
“…This is consistent with another study (37). The mortality rate in the present study was lower compared with some studies (12,38) as older rats were used in the present study instead of 3-week-old rats. Tatsuo Kawai et al (11) used a similar protocol in modeling abdominal aortic aneurysm and observed similar mortality.…”
Section: Discussioncontrasting
confidence: 53%
“…This is consistent with another study (37). The mortality rate in the present study was lower compared with some studies (12,38) as older rats were used in the present study instead of 3-week-old rats. Tatsuo Kawai et al (11) used a similar protocol in modeling abdominal aortic aneurysm and observed similar mortality.…”
Section: Discussioncontrasting
confidence: 53%
“…and ). Others have observed similar discontinuities in BAPN dose effects in vascular tissues . BAPN does not alter existing cross‐links.…”
Section: Discussionmentioning
confidence: 68%
“…Others have observed similar discontinuities in BAPN dose effects in vascular tissues. (44) BAPN does not alter existing cross-links. Thus, at the end of the experiment, each mouse is a hybrid of normal and cross-link-deficient tissues in proportions determined by the rates of tissue apposition and removal.…”
Section: Discussionmentioning
confidence: 96%
“…It is also established that irreversible inhibition of lysyl oxidase activity by administration of β-aminopropionitrile (BAPN) induces thoracic aortic aneurysms and dissections in both young turkeys and rats. 1621 The aortic pathology in BAPN-treated young rats shows features of medial degeneration, including elastin degradation, thickening of the medial layer, and SMC apoptosis. 22 Thus, inhibition of lysyl oxidase activity postnatally also induces thoracic aortic disease.…”
Section: Discussionmentioning
confidence: 99%